Building a Distributed, Asynchronous Learning Environment - Baldwin, Colin (Proceedings of the International Conference on Networked Learning, 2000)
The UniCafé project was established by a partnership between the University of Surrey (primarily the School of Educational Studies and the School of Management Studies for the Service Sector), four Further Education colleges, a Telecottage. the local library service and Tesco plc. The project aims to provide open, supported learning at a variety of traditional and non-traditional locations through electronic delivery.